2018
DOI: 10.1007/s41999-018-0084-9
|View full text |Cite
|
Sign up to set email alerts
|

Happiness of the oldest-old men is associated with fruit and vegetable intakes

Abstract: Background Positive emotions and happiness may improve health and prolong life. Diet quality, Mediterranean dietary pattern, fruit and vegetable, chocolate, and fish consumption have been linked to positive affect, improved mood, and reduced risk of depression. We examined the associations between diet, nutrition, and perceived happiness in the oldest-old men. Methods The participants in this cross-sectional analysis were the oldest-old, home-dwelling men (n = 338, mean age 88 years, range 82-97 years) from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A possible explanation for this might be that our study was conducted among the older population. Indeed, an earlier study conducted among older men also showed no positive association between fish consumption and well-being [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this might be that our study was conducted among the older population. Indeed, an earlier study conducted among older men also showed no positive association between fish consumption and well-being [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review of the observational studies analyzing the association between the intake of fruit and vegetable and mental health in adults revealed the possible beneficial influence of the indicated products. This association was studied for various aspects of mental health, ranging from general and mental well-being [35,45,49,62,68,77,82,84,94], quality of life [36,39,42,43,47,55,70], sleep quality [55], life satisfaction [50,66,82], flourishing [50], mood [50,62,68,77,81], self-efficacy [56], curiosity [68], creativity [68], optimism [91,93], self-esteem [90], stress [40,48,67,71,73,80,89,92], nervousness [82], or happiness [52,59,65,82], to anxiety [35,…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the indicated effect was studied and stated not only for fresh fruits and vegetables but also for fruit and vegetable products, such as juices [37,39,40,48,49,51,52,54,56,60,61,65,70,72,82,83,88,92,94], dried [37,49,54,66], and canned fruits and vegetables [37,38,49,50,58,65,66], salads [39,40,44,49,52,54,58,61,62,[72][73][74]89,93,94], soups [39,40,62], or ketchup [39,79], and even fo...…”
Section: Discussionmentioning
confidence: 99%
“…Food intakes were retrieved using the diet quality indices indicated as portions, deciliters, tablespoons, glasses, or frequencies per week. The portion sizes were calculated to grams and validated with 3-day food diaries obtained from a subgroup of participants; the validation procedure is explained in more detail elsewhere (5). The participants were divided into groups corresponding to their self-perceived economic situation.…”
Section: Methodsmentioning
confidence: 99%